Using pre-test to validate the Questionnaire for Website Usability (QWU) - Nur Sukinah, Aziz; Adzhar, Kamaludin (IEEE, 2015)
Usability is one of important criteria to measure website quality. One of the approaches to measure website usability is survey using questionnaire. The aim of this study is to validate the questionnaire instrument to measure the highest education institution or university website in context of usability. Pre-test are used to validate the instrument for this study. The questionnaire instrument has 9 constructs and 51 item of questionnaire. 30 respondents were involved in this study. After analyzed the result, 7 items need to delete from the instrument. Apart from the more technical and general aspects the feedback from the respondents was useful in identifying problematic questions and it was suggested that some questions need to deleted as they were seen to have same meaning with other questions and too difficult to answer for several reason such as because the sentences of the question is difficult to understand and the level of understanding between the question and respondent.